Sistem Pakar Mendiagnosa Penyakit Saraf Pusat Manusia Dengan Metode Certainty Factor - Situmeang, Nelasari; Sulindawaty, Sulindawaty (REMIK: Riset dan E-Jurnal Manajemen Informatika Komputer, 2019)
Abstract— Central nervous disease is a group of neurological disorders that affect the structure or function of the brain or spinal cord, which collectively form the central nervous system. Society in general there are still many lay people who do not understand nerve health, so many of them ignore the symptoms experienced and may be a symptom of central nervous disease. This may be due to the high cost of consultation, and not to mention doctors who are difficult to find due to time invoices. In various fields the use of technology has developed rapidly, one of which is in the field of health, one of which is the use of expert systems. Expert systems are computer programs that present and reason with the knowledge of several experts to solve problems or provide solutions. The development of technology such as expert systems is of course also supported by methods of diagnosing, such as the Certainty Factor Method. To create an expert system that can help the community in consultation about the central nervous disease experienced by the Expert System to Diagnose Human Central Nerve Disease Using the Certainty Factor Method.